TINJAUAN YURIDIS TENTANG PRINSIP KETERBUKAAN TERHADAP PENJATAHAN SAHAM PADA SAAT INITIAL PUBLIC OFFERING (PENAWARAN UMUM PERDANA) DALAM KASUS PT. NARA HOTEL INTERNASIONAL - Leo Valentino; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Basically the Disclosure Principle is a general guideline that requires issuers, public companies and other parties subject to this law to inform the public in a timely manner all material information about their business or securities that may affect the decision of investors on the securities in question and or the price of effect. Article 79 Paragraph (1) of Law Number 8 of 1995 concerning the Capital Market states that every announcement in the mass media related to a public offering is prohibited from containing untrue information about material facts and or not containing statements about material facts required for information contained in the announcement does not provide a misleading picture. This type of research can be classified in the type of empirical normative research, and the data collection technique in this research is by means of library research, and the data analysis that will be used in this research is a qualitative method, then the results of this research will be presented in descriptive and interesting terms. conclusion the author uses the Deductive method of thinking is a way of thinking that draws a conclusion from a general statement or proposition into a specific statement. From the results of the research problem there are two main things that can be concluded. First, PT Nara Hotel Internasional has not fully complied with the principles of true and timely information disclosure as evidenced by the differences in the additional information documents submitted to the public and those submitted to the OJK which were not followed by confirmation before the registration statement became effective as stipulated in Regulation IX.A.2, then the centralized allotment allocation mechanism that is oversubscribed has not complied with Regulation IX.A.7. Second, in complying with the principle of information disclosure, OJK should be able to accommodate the number of securities offered, especially centralized allotments for retail investors, this needs to be done considering that the allotment of securities is material information as regulated in the Financial Services Authority Regulation Number 31 / POJK.04 / 2015. Then At the time of the IPO, prior to obtaining an effective statement from OJK, PT Nara Hotel Internasional should first confirm the changes and/or additions to material information until OJK responds to the changes and/or additions. After that, the issuer must announce the changes and/or additions 3 (three) days before the public offering period begins.Keyword: IPO-Principle of Disclosure-Nara Hotel.